Octreotide use for rescue of vision in a pregnant patient with acromegaly. (20th May 2019) - Hannon, Anne Marie; Frizelle, Isolda; Kaar, George; Hunter, Steven J; Sherlock, Mark; Thompson, Christopher J; O'Halloran, Domhnall J; ,
Summary: Pregnancy in acromegaly is rare and generally safe, but tumour expansion may occur. Managing tumour expansion during pregnancy is complex, due to the potential complications of surgery and side effects of anti-tumoural medication. A 32-year-old woman was diagnosed with acromegaly at 11-week gestation. She had a large macroadenoma invading the suprasellar cistern. She developed bitemporal hemianopia at 20-week gestation. She declined surgery and was commenced on 100 µg subcutaneous octreotide tds, with normalisation of her visual fields after 2 weeks of therapy. She had a further deterioration in her visual fields at 24-week gestation, which responded to an increase in subcutaneous octreotide to 150 µg tds. Her vision remained stable for the remainder of the pregnancy. She was diagnosed with gestational diabetes at 14/40 and was commenced on basal bolus insulin regimen at 22/40 gestation. She otherwise had no obstetric complications. Foetal growth continued along the 50th centile throughout pregnancy. She underwent an elective caesarean section at 34/40, foetal weight was 3.2 kg at birth with an APGAR score of 9. The neonate was examined by an experienced neonatologist and there were no congenital abnormalities identified. She opted not to breastfeed and she is menstruating regularly post-partum. She was commenced on octreotide LAR 40 mg and referred for surgery. At last follow-up, 2 years post-partum, the infant has been developing normally. In conclusion, our case describes a first presentation of acromegaly in pregnancy and rescue of visual field loss with somatostatin analogue therapy. Learning points: Tumour expansion may occur in acromegaly during pregnancy. Treatment options for tumour expansion in pregnancy include both medical and surgical options. Somatostatin analogues may be a viable medical alternative to surgery in patients with tumour expansion during pregnancy.